Problems of proving in criminal proceedings based on violations of war laws and customs - A. V. Shulzhenko (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article is devoted to the peculiarities of conducting a pre-trial investigation into violations of the laws and customs of war. The purpose of the work is a theoretical generalization of the problems of proving existing in practical activities during the investigation of crimes related to violations of war laws and customs. Recently, a significant number of incidents of shelling of residential areas from the territory of the Russian Federation have been recorded in Ukraine, which led to violations of criminal proceedings, which are currently being investigated by the investigators of the National Police. During the investigation, a number of problems related to the process of proof has arisen, which makes this problem relevant. There are problems with the lack of experience of the investigators for the specified facts, as well as with objective reasons. The latter includes the commission of illegal actions from the territory of another state, not under the control of Ukraine, which significantly complicates the process of establishing of the subjects of criminal acts during the investigation, the locations of military units from which shelling of Ukrainian territory, where civilians are located, is carried out. It is also a problem to determine the forms of criminal activity of subjects, namely by proving complicity or its absence. An analysis of investigative (search) actions is provided, including inspection of the scene, investigation, examination of the corpse, exhumation, appointment and conducting of forensic examinations. Among the examinations, it is advisable to appoint forensic medical, commodity science, economic, fire engineering, construction engineering, etc. The most common problem is the impossibility of identifying the suspect, questioning, detaining, and conducting other procedural actions with them. Conducting an investigative experiment is also excluded. It is proposed to establish operational cooperation between investigators and the Security Service of Ukraine, to develop a unified methodology for investigating crimes related to violations of the laws and customs of war. It is also proposed to establish operational interdepartmental relations, the results of which could be used in evidentiary activities.